Hubungan Health Compromosing Behavior Dengan Stres Kerja Pada Pekerja PT. PLN (Persero) UP3 Makassar Utara - Nur Igrahi Khusy Arahbia; Rezky Aulia Yusuf; Septiyanti (Window of Public Health Journal, 2025)
Work stress is when a person faces a task or job that cannot or cannot yet be reached by his abilities. This study aims to determine the factors compromising health behavior with work stress in PT workers. PLN (PERSERO) UP3 North Makassar in 2023. This type of research uses a quantitative research method with a descriptive approach with a cross-sectional study design. The population in this study was 52 workers using a sampling technique, namely total sampling, which is the workers of PT. PLN (PERSERO) UP3 North Makassar. Data were obtained using a questionnaire and analyzed using the chi-square test at the confidence level (alpha = 0.05). The results showed that there was a significant relationship between smokers/smoking and work stress, namely (p-value = 0.010 <0.05). There was no significant relationship between physical activity and work stress (p-value = 0.203 >0.05). There was no significant relationship between sleep quality and work stress (p-value = 0.026 <0.05). There is a significant relationship between eating patterns and work stress, namely (p-value = 0.000 > 0.05) for workers of PT. PLN (PERSERO) UP3 North Makassar in 2023. From the results of this study, researchers suggest that companies provide socialization regarding health regarding the dangers of smoking behavior and increase efforts regarding eating patterns for workers to reduce stress; it is hoped that workers sleep according to human needs both in terms of time and duration, workers should do light exercise in the morning before work so that it can help relieve stress.